Demographic, residential, and socioeconomic effects on the distribution of 19th century white Body Mass Index values - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2011)
Little research exists on the body mass index values of 19th century Americans of European descent. Using a new BMI data set and robust statistics, between 1860 and 1880, BMIs decreased across the distribution; however, after 1880, BMIs in the highest quantiles increased, while those in lower BMI quantiles continued to decrease. Late 19th and early 20th century white BMIs increased at older ages in higher quantiles and decreased in lower quantiles, indicating significant net biological disparity by age. During industrialization, white BMIs were lower in Kentucky, Missouri, and urban Philadelphia.
Keywords: I10; 330; body mass index; 19th century race relations; Lebensstandard; Farbige Bevölkerung; Weiße; Klima; Soziale Ungleichheit; Körpergewicht; USA